Digitization trends: the growing demand for smart event management systems among small entrepreneurs in developing regions - Mohd Sakeri, Muhammad Nur Asri; Mohamad Rosman, Mohamad Rahimi; Fadzil, Faizal Haini; Abdullah, Nurulannisa; Arshad, Izzatil Husna; Mohd Zawawi, Mohd Zafian; Md. Saleh, Mohamad Sayuti (Faculty of Information Management, 2025)
Interaction problems often arise between event managers and participants in making an event a success. This is due to the use of WhatsApp and Telegram group applications which are no longer relevant to be used as the main medium in managing events especially among small entrepreneurs. Therefore, a smart event management system known as SmartEMS is introduced to offer a complete function in managing events and is more user-friendly. The method used in collecting data for this study to identify every problem that arises with the existing event management system is conducted through interview sessions and analysis of existing studies related to this issue. The collected data was analyzed thematically to obtain clear and accurate analysis results regarding the user's needs for the system. In conclusion, SmartEMS can be developed and used to meet the main needs of users, which is a complete function in managing events and is more userfriendly.